2019
DOI: 10.1021/acsaem.9b00304
|View full text |Cite
|
Sign up to set email alerts
|

Structural Monitoring of NiBi Modified BiVO4 Photoanodes Using in Situ Soft and Hard X-ray Absorption Spectroscopies

Abstract: Photoelectrochemical (PEC) water splitting, a process using solar light and a semiconductor to split water, is proposed as a potentially scalable method to store solar energy through renewable H 2 fuels. Obtaining the electronic structure information on co-catalyst is a crucial step toward gaining a mechanistic understanding of the water oxidation reaction of this catalyst. In the present work, we show that the PEC performance of BiVO 4 photoanodes can be enhanced by the deposition of a nickel−borate co-cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In a recent work by Xi et al [ 83 ], it was shown that PEC performance of BiVO 4 photoanodes can be enhanced by the deposition of a NiB i co-catalyst layer. The electronic structure of NiB i has been probed by in situ soft and hard XAS spectroscopy by monitoring the signal at Ni L and K edges and the O K edge under different potential and illumination conditions.…”
Section: Pec In Situ and Operando Synchrotron Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work by Xi et al [ 83 ], it was shown that PEC performance of BiVO 4 photoanodes can be enhanced by the deposition of a NiB i co-catalyst layer. The electronic structure of NiB i has been probed by in situ soft and hard XAS spectroscopy by monitoring the signal at Ni L and K edges and the O K edge under different potential and illumination conditions.…”
Section: Pec In Situ and Operando Synchrotron Studiesmentioning
confidence: 99%
“…The advantages of this cell for the study of solids, liquids and solid/liquid interfaces under operando conditions were summarized by the authors as follows: (i) the possibility to measure XAS in transmission and fluorescence mode simultaneously, (ii) fast sample/membrane replacement (less than 5 min), (iii) reduced risk of beamline contamination with electrolyte solution due to two protection membranes and (iv) manipulation of the sample with visible light. This cell has been successfully used in a sequence of soft XAS operando studies of Ni- and Mn-modified BiVO4 photoanodes [ 83 , 101 ] and MnO [ 85 ] water oxidation catalysts.…”
Section: Pec In Situ and Operando Synchrotron Studiesmentioning
confidence: 99%
“…25 Through these methods, the charge separation and transfer on both the surface and within the bulk of the photoanode can be effectively improved. In recent years, researchers have found that employing cocatalysts such as cobalt oxide (CoO x ), 26 cobalt borate (CoB i ), 27 cobalt phosphate (CoP i ), 28 iron oxyhydroxide (FeOOH), 29 iron oxyhydroxide/cobalt oxyhydroxide (FeOOH/CoOOH) 30 and nickel borate (NiB i ) 31,32 is an effective method to modify the performance of photoanodes for enhanced photocatalysis. Studies by Lifei Xi et al 33 demonstrated that cobalt borate (CoB i ) films exhibited higher activity than CoB i with increasing film thickness, ultimately displaying superior performance.…”
Section: Introductionmentioning
confidence: 99%